Answer:
y=-5x-2
Step-by-step explanation:
y=mx+b
where m is the slope
y=-5x+b
to solve for b, which is the y intercept, plug in (1,-7)
-7=-5(1)+b
-7=-5+b
-2=b
y=-5x-2
Answer:
y = -3x + 21
Step-by-step explanation:
(5,6)
y = mx + b
6 = -3 × 5 + b
solving for b
b = 6 - (-3)(5)
b = 21
Therefore,
y = -3x + 21
Answer:
a.) -18 x 10^6
Step-by-step explanation:
multiply 9 x-2
add exponents 9 and -3
<h2>
<em><u>My</u></em><em><u> </u></em><em><u>equation</u></em><em><u> </u></em></h2>
<em>f</em><em>(</em><em>x</em><em>=</em><em>x</em><em>^</em><em>2</em><em> </em><em>is</em><em> </em><em>30</em><em> </em><em>and</em><em> </em><em>g</em><em>(</em><em>x</em><em>)</em><em> </em><em>=</em><em>4 1</em><em> </em><em> </em><em>is</em><em> </em><em>50</em><em>.</em><em>1</em>
<em>Hope</em><em> </em><em>it</em><em> </em><em>helps</em><em> </em><em>#brainliestbunch</em><em> </em><em>=</em><em>)</em><em> </em>
Answer:
A) log(jk2y = 7log i + 2logk
Step-by-step explanation: